2012
DOI: 10.3347/kjp.2012.50.4.375
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Vivax Malaria

Abstract: Malaria is still a leading cause of morbidity and mortality. The increase in lipid peroxidation reported in malaria infection and antioxidant status may be a useful marker of oxidative stress during malaria infection. The aim of this study was to investigate the role of antioxidant enzymes against toxic reactive oxygen species in patients infected with Plasmodium vivax and healthy controls. Malondialdehyde levels, superoxide dismutase, and glutathione peroxidase activities were determined in 91 P. vivax patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 17 publications
4
31
0
1
Order By: Relevance
“…The mean erythrocyte concentration of SOD was significantly lower in patients than healthy subjects. Several studies reported reduction of SOD activities of erythrocytes in patients with malaria [15][16][17][18], which confirms results obtained. This affirms its role as an antioxidant, where levels decreased in an effort to offset the oxidant stress.…”
Section: Discussionsupporting
confidence: 81%
“…The mean erythrocyte concentration of SOD was significantly lower in patients than healthy subjects. Several studies reported reduction of SOD activities of erythrocytes in patients with malaria [15][16][17][18], which confirms results obtained. This affirms its role as an antioxidant, where levels decreased in an effort to offset the oxidant stress.…”
Section: Discussionsupporting
confidence: 81%
“…This was more common in P. vivax and mixed infection than P. falciparum infection. Our findings regarding the reduction in SOD level with that of severity of malarial infection is in correlation with the studies done by Erel et al, Bilgin et al and Narsaria et al 12,24,25 The SOD levels though not specific for malaria, along with positive parasite identification could be a sensitive indicator for severity of malaria infection.…”
Section: Discussionsupporting
confidence: 92%
“…12 Bilgin et al in their study found the activities superoxide dismutase and glutathione peroxidase were found to be significantly lower in vivax malaria patients. 24 Narsaria et al also found that there is significant elevation of malondialdehyde and protein carbonyl levels reflect the increased oxidative stress, whereas decreased levels of glutathione and superoxide dismutase point toward utilization of the antioxidants in severe malaria. 25 Thus, these changes in oxidants and antioxidants suggests the production of reactive oxygen species and their possible role in pathogenesis of severe malaria.…”
Section: Discussionmentioning
confidence: 97%
“…Es característico en la parasitemia por Plasmodium la actividad muy dinámica de las enzimas oxidantes y antioxidantes [18][19][20] . En esta infección se disminuyen las enzimas con función anti-oxidante (catalasas, superóxido dismutasas, glutation peroxidasas) pudiendo generar especies reactivas del oxígeno y que los fármacos antimaláricos (cloroquina y primaquina) aumentan la producción de ERO en linfocitos y macrófagos para la destrucción del microorganismo 1 .…”
Section: Discussionunclassified